2017
DOI: 10.3906/tar-1610-57
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and potential genetic resources of several Romanian larch populations

Abstract: decidua (European larch) has a scattered natural area and is present in four geographic zones (Alps, Sudetan Mountains, Carpathians, and Central Poland), where local European larch have sometimes the status of subspecies or varieties (Biswas and Mohri, 1997). In Romania, the larch has a natural range, being gathered into 5 genetic centers: Ceahlau Mountains (1400-1450 m altitude), Ciucas (1000-1450 m), Bucegi (1200-1500 m), Lotru Mountains (670-1900 m with a maximum range in this area), and Apuseni Mountains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
2
0
1
Order By: Relevance
“…For example, despite their relative geographical proximity, the five populations from the northwestern part of Romania did not display closer genetic distances between them than with those farther away. A similar phenomenon was reported in Romanian populations of Larix decidua [59,60]. Cluster analysis confirmed that the genetic relationships between populations were only marginally associated with geographical distances.…”
Section: Discussionsupporting
confidence: 85%
“…For example, despite their relative geographical proximity, the five populations from the northwestern part of Romania did not display closer genetic distances between them than with those farther away. A similar phenomenon was reported in Romanian populations of Larix decidua [59,60]. Cluster analysis confirmed that the genetic relationships between populations were only marginally associated with geographical distances.…”
Section: Discussionsupporting
confidence: 85%
“…It should be mentioned that only three (Latorit , a, Bucegi, and Apuseni) out of the five naturally occurring areas of larch in Romania are found in breeding populations. On the other hand, we still lack information about the level of diversity of the source populations of plus trees, with the exception of the Baciu seed orchard (northwestern part of Romania) [51].…”
Section: Discussionmentioning
confidence: 99%
“…Although the tests for identifying the offspring of seed orchards are still at the beginning stage [20], genotypic evaluation is useful for correcting inherent errors related to mature seed orchards (e.g., the origin of clones) and for providing alternative support for the interpretation of the performances in phenotypic traits. With the exception of the Baciu seed orchard (from the northwestern region of Romania) [51], we know little about the diversity of the source populations of plus trees. In evaluating the germplasm collections constructed to obtain desirable traits, the final extracted core collection increased the rate of allele preservation, incorporated every allele from the entire collection, and provided candidate resources for the enhanced breeding of larch.…”
Section: Discussionmentioning
confidence: 99%
“…Поэтому интерес к представителям данного рода ни в России [1][2][3], ни за ее пределами [4][5][6][7][8][9][10] не ослабевает. Проводятся активные исследования систематики, физиологии, межвидового разнообразия и внутривидового полиморфизма рода Лиственница по широкому спектру признаков и свойств, имеющих хозяйственное, адаптационное и идентификационное значение [1][2][3][11][12][13][14][15][16][17][18]. Пигментный состав листового аппарата во многом определяет параметры фотосинтеза и в конечном итоге продуктивность и устойчивость древесных растений [19][20][21][22][23].…”
unclassified